Mostar in Turkish Poetry of XVII century - Mušić, Omer (Prilozi za orijentalnu filologiju, 2017)
In addition to Sarajevo, the town that numerous poems had been written about (M. Hanžić, “Sarajevo u turskoj pjesmi”, Glasnik IVZ, Sarajevo, 1943, No. 7-12; O. Mušić, “Jedna turska pjesma o Sarajevu iz XVII vijeka”, Prilozi III-IV, Sarajevo, 1952-53, pp. 575-587), Mostar is another town that our people wrote poems about in Turkish. Along with Sarajevo and its mosques, schools, public baths, libraries, guest-houses and fountains - Mostar became one of the most prominent towns in Herzeg-Bosnia and gave us, relatively, the largest number of learned men and poets. Along with biographical data on the famous poet of Mostar, Derviš-pasha Bajezidagić, Dr. Safet-beg Bašagić also published his eulogy about Mostar and eight freely translated verses (Dr. Safet-beg Bašagić, Bošnjaci i Hercegovci u islamskoj književnosti, Sarajevo, 1912, pp. 39-50). He published na- zirah (parallel) from Derviš-pasha’s ode to Mostar, and only two verses of the ode by “someone called Derviš-effendi of Mostar” with no additional comments (ditto, pp. 43-87). In this paper, these two poems, by the two Dervišes of Mostar, the one by Derviš-pasha Bajezidagić had nine rather than eight lines, unlike the version published by Bašagić. In comparison to the ode by Derviš-pasha, the poem about Mostar by hajji Derviš-effendi also had nine lines. Comparing the two poems about Mostar, one may conclude that the one by Derviš-efendi is as rich as Derviš-pasha’s in terms of descriptions and the beauty of language. Although Bašagić thought that Derviš-effendi’s one “lags behind its paragon, and not close to it”, this opinion is unfounded. A poem about Mostar by a thus far unknovvn poet, Tabi of Mostar, was published along these two. There are 13 lines of the same metre (el-hezeg), same as the poems by the two Dervišes, and in its descriptions and beauty of the language it is no less beautiful than the poetry of the other two described above. The famous arched bridge over River Neretva in Mostar was particularly referred to in ali three poems. This bridge, the attraction of Mostar even today, inspired also a poet named Medžazi, who wrote extraordinary verses about it. Medjatija’s poem is full of allegories and metaphors of abstract, hardly un- derstandable comparison. This is probably why Bašagić did not even attempt to translate Medžazija’s poetry. Of it, Bašagić said that it was one of “truly mysterious metaphors” (ditto, p. 56). There are seventeen lines, mostly detailed descriptions of the bridge, and some are difficult to understand because of the picturesque comparisons. This was probably the reason why Bašagić so resolutely rejected Medžazi as a poet. The poet Husein-effendi Catrnja wrote three poems, describing the skill of the rope-dancing acrobats, dancing fearlessly on a rope stretched above the bridge from one side of the river to the other. He said that they accompli- shed something “not done ever before by either Arabs, Persians or Latins.” Here the poet compares life with the acrobat’s walk över the rope and advises people to live in this world honestly and religiously, to enjoy salvation in the next. The construction of the bridge and the fortress, and the reconstruction of the Mostar water supply were mentioned by anonymous poets in skilfully constructed chronograms. According to ebjed, the following dates were mentioned: construction of the bridge 973 H - 1566-67, construction of the fortress 1108 H - 1696-97, reconstruction of the water supply 1113 H- 1701-2. It should be emphasised that the last verse of the chronogram on the water supply reconstruction is a rare example of knovvledge and skill of the anonymous poet. This chronogram contains dates represented as the sum total of numerical values of Ietters with diacritical signs in the first half of the line and in the other the sum total of numerical values of the Ietters with no diacritical signs.